A Greener Approach for the Regioselective Synthesis of Multifunctionalized Indolylpyrrole and Indolyltriazolylpyrrole Hybrids via Michael Addition of α-Azido Ketones - Kamalraja, Jayabal; Sowndarya, Ramachandran; Perumal, Paramasivan Thirumalai (Synlett, 2014)
A convergent synthesis of indolylpyrrole derivatives has been developed from domino coupling of α-azido ketones, aromatic aldehydes, and 3-cyanocetylindoles in the presence of piperidine in aqueous medium at 80 °C via cascade Knoevenagel condensation–Michael addition–annulation in excellent yields. Further, the synthesized ortho-azidoindolylpyrroles undergo [3+2] cycloaddition with phenyl acetylene to give indolyltriazolylpyrrole hybrids in good yields. This domino transformation, efficiently generates C–C and C–N bonds in a minimum of synthetic steps resulting in three important bioactive heterocyclic frameworks, indole–pyrrole–triazole hybrids.
Keywords: domino reaction; greener approach; α-azido ketones; regioselective synthesis; indolylpyrroles; indolyltriazolylpyrroles